Loss-of-Function Variants in MYLK Cause Recessive Megacystis Microcolon Intestinal Hypoperistalsis Syndrome. - Halim, Danny; Brosens, Erwin; Muller, Françoise; Wangler, Michael F; Beaudet, Arthur L; Lupski, James R; Akdemir, Zeynep H Coban; Doukas, Michael; Stoop, Hans J; de Graaf, Bianca M; Brouwer, Rutger W W; van Ijcken, Wilfred F J; et al. (Am J Hum Genet, 2017)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) is a congenital disorder characterized by loss of smooth muscle contraction in the bladder and intestine. To date, three genes are known to be involved in MMIHS pathogenesis: ACTG2, MYH11, and LMOD1. However, for approximately 10% of affected individuals, the genetic cause of the disease is unknown, suggesting that other loci are most likely involved. Here, we report on three MMIHS-affected subjects from two consanguineous families with no variants in the known MMIHS-associated genes. By performing homozygosity mapping and whole-exome sequencing, we found homozygous variants in myosin light chain kinase (MYLK) in both families. We identified a 7 bp duplication (c.3838_3844dupGAAAGCG [p.Glu1282_Glyfs51]) in one family and a putative splice-site variant (c.3985+5C>A) in the other. Expression studies and splicing assays indicated that both variants affect normal MYLK expression. Because MYLK encodes an important kinase required for myosin activation and subsequent interaction with actin filaments, it is likely that in its absence, contraction of smooth muscle cells is impaired. The existence of a conditional-Mylk-knockout mouse model with severe gut dysmotility and abnormal function of the bladder supports the involvement of this gene in MMIHS pathogenesis. In aggregate, our findings implicate MYLK as a gene involved in the recessive form of MMIHS, confirming that this disease of the visceral organs is heterogeneous with a myopathic origin.
Keywords: Abnormalities, Multiple; Base Sequence; Colon; Female; Genes, Recessive; Homozygote; Humans; Intestinal Pseudo-Obstruction; Male; Mutation; Myosin-Light-Chain Kinase; Pedigree; Urinary Bladder